2018
DOI: 10.3389/fimmu.2018.02588
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 30 Deficiency Attenuates Chronic but Not Acute Phases of Experimental Autoimmune Encephalomyelitis Through Induction of Neuroprotective Microglia

Abstract: Glial connexins (Cxs) form gap junction channels through which a pan-glial network plays key roles in maintaining homeostasis of the central nervous system (CNS). In multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE), expression of astrocytic Cx43 is lost in acute lesions but upregulated in chronic plaques, while astrocytic Cx30 is very low in normal white matter and changes in its expression have not been convincingly shown. In Cx30 or Cx43 single knockout (KO) mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 77 publications
0
12
1
Order By: Relevance
“…It is known that microglial dynamic conversion from resting to activated is accompanied by a retraction of the cellular processes into the cell body (Kettenmann et al, 2011). The subjective (Davis et al, 1994; Kloss et al, 2001; Norden et al, 2016) and objective (Kozlowski and Weimer, 2012; Davis et al, 2017; Fang et al, 2018) evaluation of the circularity have shown that roundness is directly related to microglial activation. Similarly, in the present study the greater the circularity, the higher the degree of inflammatory activation, a fact that is clearly evidenced in cluster 4.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that microglial dynamic conversion from resting to activated is accompanied by a retraction of the cellular processes into the cell body (Kettenmann et al, 2011). The subjective (Davis et al, 1994; Kloss et al, 2001; Norden et al, 2016) and objective (Kozlowski and Weimer, 2012; Davis et al, 2017; Fang et al, 2018) evaluation of the circularity have shown that roundness is directly related to microglial activation. Similarly, in the present study the greater the circularity, the higher the degree of inflammatory activation, a fact that is clearly evidenced in cluster 4.…”
Section: Discussionmentioning
confidence: 99%
“…Gene set enrichment analysis showed a decreased proinflammatory cytokine gene set and increased expression of the anti‐inflammatory gene set. The numbers of microglia and astroglia were increased in Cx30 KO mice, but the clinical course was ameliorated because of the anti‐inflammatory activation of glial cells 26 …”
Section: Cx30‐deficient Micementioning
confidence: 75%
“…These mice were not different either in terms of the degree of immune cell reactivity in the spinal cord, evaluated using ionized calcium binding adaptor molecule 1 (Iba1) immunostaining at the endpoint of clinical evaluation. Interestingly, the global Cx30 deficiency reduced the severity of the chronic phase (8 weeks after the insult) in this model and this effect was correlated with the emergence of an anti-inflammatory phenotype in both spinal cord astrocytes and microglia (Fang et al, 2018). Given that a reduction in the abundance of Cx43 during the chronic phase of experimental autoimmune encephalomyelitis was observed in global Cx30 deficient mice, the neuroprotective effect could be mediated indirectly via astrocytic Cx43.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 86%